Structure-reinforced silicon-based electrode for lithium battery as well as preparation method and application of structure-reinforced silicon-based electrode
By in situ polymerizing organic/inorganic hybrid buffer connectors in silicon electrodes to form a stable electrode structure and rich artificial SEI layer, the stability and toughness problems caused by volume changes in silicon electrodes during charging and discharging are solved, and the performance and life of lithium-ion batteries are significantly improved.
Patent Information
- Application Number
- CN202411681197.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silicon electrodes have poor stability and toughness due to volume changes during charging and discharging, which affects the performance and life of lithium-ion batteries.
Through the in-situ polymerization strategy, organic/inorganic hybrid buffer connectors are uniformly filled in situ in the pores of the powder electrode, tightly connecting the electrode components, and a rich artificial solid electrolyte interface film (SEI) is formed on the surface of silicon particles, improving the mechanical stability of the electrode structure.
The initial Coulomb efficiency and cycling performance of lithium-ion batteries are significantly improved, ensuring high capacity retention and long cycle life.
Smart Images

Figure CN119673974A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a structurally reinforced silicon-based electrode for lithium batteries and a preparation method and application thereof. Background Art
[0002] To meet the growing demand for consumer electronics and electric vehicles, lithium-ion batteries (LIBs) need to have higher energy density and longer cycle life. Silicon anode has obvious advantages over traditional commercial graphite anode: First, the Li generated by silicon anode in deep lithium state 15 Si4 corresponds to 4200mAh g -1 In contrast, the theoretical capacity of LiC6 generated by deep lithiation of graphite anode is only 372 mAh g -1 ; Secondly, silicon has a lower electrochemical potential (~0.2V vs.Li + / Li); finally, silicon is also relatively abundant in nature, which makes it an ideal negative electrode material for lithium-ion batteries. However, during the charge and discharge process, the (de)lithiation reaction experienced by the silicon negative electrode is accompanied by repeated (de)alloying reactions. This process causes a dramatic volume change in the silicon electrode, which can usually reach about 300%. Such a huge volume effect will cause a series of problems, such as the pulverization of silicon particles, which will not only lead to the loss of active materials, but also make the solid electrolyte interface (SEI) unstable. Ultimately, this unstable electrode interface may lead to the collapse of the electrode, which will seriously affect the performance and life of the battery.
[0003] To address the above problems, researchers have proposed a variety of strategies, including limiting the size of silicon, surface modification, and optimization of electrode binders to obtain silicon electrodes with high mechanical strength and stable interfaces. Studies have shown that the use of silicon nanoparticles or porous structures is very effective in improving the cycling stability of silicon-based electrodes. However, the preparation cost of these active materials is generally high. In addition, carbon-based materials and various other inorganic coatings have been proposed to enhance the stability of silicon anodes, but they generally exhibit poor toughness when undergoing large volume changes. Therefore, it is more reasonable to coat a functionalized polymer layer on the silicon surface to alleviate volume expansion and construct a good artificial solid electrolyte interface (SEI). In addition, some inorganic substances, such as lithium fluoride (LiF), lithium nitride (Li3N), lithium oxide (Li2O), etc., are also considered suitable for silicon anodes because they have higher Young's modulus and ionic conductivity. Summary of the invention
[0004] In order to solve the above-mentioned problems of poor stability and poor toughness in existing silicon electrodes, the present invention provides a structurally reinforced silicon-based electrode for lithium batteries and a preparation method and application thereof. The silicon-based electrode uses an in-situ polymerization strategy to uniformly fill the pores in the powder electrode with an organic / inorganic hybrid buffer connector in situ. The connector can tightly connect the components such as the current collector, active material, binder and conductive agent in the powder electrode, construct a structurally stable electrode structure, and form a rich artificial SEI layer on the surface of the electrode Si (silicon) particles, thereby significantly improving the mechanical stability of the electrode structure.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing a structurally reinforced silicon-based electrode for a lithium battery of the present invention comprises the following steps:
[0007] (1) Mixing 5% to 10% of a polymer monomer, 1% to 25% of a ring-opening catalyst and 65% to 94% of an organic solvent by mass fraction to obtain a precursor solution, wherein the polymer monomer is one or more of 1,2-propylene oxide, 1,3-dioxolane or 1,3,5-trioxane, and the ring-opening catalyst is one or more of lithium difluorooxalatoborate (LiODFB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LIFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiF4), anhydrous aluminum chloride (AlCl3), boron trifluoride (BF3), ferric chloride (FeCl3), zinc chloride (ZnCl2), titanium tetrachloride (TiCl4), tin trichloride (SnCl4), antimony pentachloride (SbCl5) or ferric bromide (FeBr3);
[0008] (2) In an inert gas protection and water-free environment, the precursor solution is added to the silicon-based powder electrode, and allowed to stand to allow the precursor solution to fully infiltrate the powder electrode and penetrate into the gaps in the powder electrode, thereby fully contacting the current collector, active material, binder and conductive agent of the electrode;
[0009] (3) Heating at 25 to 100° C. to initiate an in-situ ring-opening polymerization reaction of the polymer monomer to obtain an organic-inorganic hybrid, wherein the organic-inorganic hybrid tightly connects the current collector, active material, binder and conductive agent in the powder electrode to construct a mechanically stable electrode structure and form a rich artificial SEI film on the electrode surface.
[0010] Taking 1,3,5-trioxane as a polymer monomer and lithium difluorooxalatoborate as a ring-opening catalyst as an example, the organic / inorganic hybrid obtained by the above preparation method has an organic component of poly 1,3,5-trioxane (PTXE) and an inorganic component of LiF, BO and FB. The organic / inorganic hybrid tightly connects the components of the current collector, active material, binder and conductive agent in the powder electrode, constructs a stable electrode structure, and forms an excellent SEI layer with rich LiF / BO / FB components on the surface of the electrode Si particles, wherein the reaction formula involved in the inorganic components LiF, BO and BF of the hybrid is shown in the following formula (I-II), and the organic component of the hybrid has a reaction formula shown in the following formula (III);
[0011]
[0012] LiBF4BF3+LiF(II)
[0013]
[0014] The present invention uses Lewis acid as an initiator and epoxy compound as a Lewis base, and utilizes oxygen atoms rich in electrons to attack Lewis acid to form oxygen cations, so that the carbon adjacent to the oxygen cations is positively charged, and the positively charged carbon atoms are attacked by the oxygen atoms of the epoxy compound to open the ring, and the organic polymer is obtained in this cycle. At the same time, corresponding inorganic components are generated, such as the above-mentioned 1,3,5-trioxane as a polymer monomer and lithium difluorooxalatoborate as a ring-opening catalyst. The present invention can also use lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LIFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiF4), anhydrous aluminum chloride (AlCl3), boron trifluoride (BF3), ferric chloride (FeCl3), zinc chloride (ZnCl2), titanium tetrachloride (TiCl4), tin trichloride (SnCl4), antimony pentachloride (SbCl5) or ferric bromide (FeBr3) as ring-opening initiators to provide empty orbitals of Lewis acids, and 1,2-propylene oxide or 1,3,5-trioxane as epoxy compounds to provide lone pairs of electrons of Lewis bases.
[0015] In one embodiment of the present invention, the organic solvent is one or more of fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate or ethylene glycol dimethyl ether.
[0016] In one embodiment of the present invention, the organic solvent is fluoroethylene carbonate.
[0017] In one embodiment of the present invention, the polymer monomer is 1,3-dioxolane or 1,3,5-trioxane.
[0018] In one embodiment of the present invention, the ring-opening catalyst is lithium difluorooxalatoborate or lithium bis(trifluoromethanesulfonyl)imide.
[0019] In one embodiment of the present invention, by mass fraction, the amount of the polymer monomer is 6.85%, the amount of the ring-opening catalyst is 23.84%, and the amount of the organic solvent is 69.31%.
[0020] In one embodiment of the present invention, step (2) is carried out in a glove box under argon protection with a water content and an oxygen content both less than 1 ppm.
[0021] In one embodiment of the present invention, the heating temperature in step (3) is 80°C.
[0022] The invention also discloses a silicon-based electrode prepared by the silicon-based electrode preparation method.
[0023] The invention also discloses the application of the silicon-based electrode in a lithium battery.
[0024] The invention also discloses a lithium battery, which uses the silicon-based electrode as a negative electrode.
[0025] Optionally, a lithium battery of the present invention comprises a positive electrode plate, a structurally reinforced silicon-based electrode (negative electrode plate), a separator, an electrolyte and a shell, wherein the electrolyte is formulated as 1.0M LiPF6 dissolved in a mixed solution of ethylene carbonate / dimethyl carbonate (EC / DMC (volume ratio 1:1)), with 10% FEC added as an additive; the positive electrode plate is coated with a positive electrode slurry formed by mixing an active material, a conductive agent carbon black, and a binder polyvinylidene fluoride in a weight ratio of 8:1:1 on a positive electrode current collector A1 foil; the active material is selected from a lithium nickel cobalt manganese oxide LiNi with a chemical formula of x Co y Mn z O2 (NCM), lithium iron phosphate (LiFePO4) or lithium cobalt oxide (LiCoO2) one or more; the silicon-based electrode is composed of a conventional powder electrode (current collector, active material, conductive agent, binder) and an organic-inorganic hybrid buffer filled in situ into the pores of the powder electrode, and the weight ratio of the active material, conductive agent carbon black and binder polyacrylic acid in the silicon-based electrode is 8:1:1; the active material is selected from one or more of nano-silicon, micro-silicon, silicon oxide, SiOx or silicon-carbon material.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention is a structurally reinforced silicon-based electrode for lithium batteries. The polymerizable precursor solution penetrates into the gaps of the active particles of the electrode by utilizing the pores contained in the powder electrode, and fully contacts with the components of the powder electrode such as the current collector, active material, binder and conductive agent, and then initiates an in-situ polymerization reaction under heating conditions to enhance the electrode structure. At the same time, the decomposition product of the salt in the precursor solution is uniformly mixed with the polymer to form an organic / inorganic hybrid elastomer, which has a high Young's modulus and lithium ion conductivity and is covered on the surface of the silicon particles as an artificial SEI. Thanks to the structural reinforcement and interface improvement, the lithium-ion battery prepared by using the silicon-based electrode of the present invention as the negative electrode shows a high initial coulomb efficiency (ICE) of 85.1% and excellent cycle performance (after 300 cycles at 1.0A / g, the specific capacity is higher than 2000mAh / g, and the capacity retention rate is greater than 80%). BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The scanning electron microscope images of the electrode plane and cross section of Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 1 (a, c) are comparative example 1, Figure 1 (b, d) are Example 1;
[0029] Figure 2 The digital photos of Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 2 (a) is Comparative Example 1 and Figure 2 (b) is embodiment 1;
[0030] Figure 3 The Fourier transform infrared spectra of the polymer monomers before and after polymerization of Example 1 of the present invention;
[0031] Figure 4 This is an X-ray photoelectron spectroscopy (XPS) graph of the structurally reinforced silicon-based electrode for lithium batteries of Example 1 of the present invention;
[0032] Figure 5 A comparison chart of the cycle performance of the silicon-based electrodes of Example 1 of the present invention and Comparative Example 1 applied to lithium-ion batteries (Si / / Li);
[0033] Figure 6 This is a performance comparison chart of the first 200 cycles of applying the silicon-based electrodes of Example 2 and Comparative Example 2 to lithium-ion batteries (NCM811 / / Si);
[0034] Figure 7 is a scanning electron microscope image of a cross section of an electrode according to Example 3 of the present invention;
[0035] Figure 8 The Fourier transform infrared spectra of the polymer monomer of Example 3 before and after polymerization;
[0036] Fig. 9 The cycle performance diagram of applying the silicon-based electrode of Example 3 to a lithium-ion battery (Si / / Li);
[0037] Fig.10 The cycle performance diagram of applying the silicon-based electrode of Example 4 to a lithium-ion battery (Si / / Li);
[0038] Fig.11 This is a schematic diagram of the structure of a structurally reinforced silicon-based electrode for a lithium battery according to an embodiment of the present invention;
[0039] Fig.12 It is a comparison chart of 180° peeling test of electrode surfactants of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0041] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0042] A method for preparing a structurally reinforced silicon-based electrode for a lithium battery according to an embodiment of the present invention comprises the following steps:
[0043] (1) Mixing 5% to 10% of a polymer monomer, 1% to 25% of a ring-opening catalyst and 65% to 94% of an organic solvent by mass fraction to obtain a precursor solution, wherein the polymer monomer is one or more of 1,2-propylene oxide, 1,3-dioxolane or 1,3,5-trioxane, and the ring-opening catalyst is lithium difluorooxalatoborate (LiODFB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LIFSI), hexafluoroethane One or more of lithium fluorophosphate (LiPF6), lithium tetrafluoroborate (LiF4), anhydrous aluminum chloride (AlCl3), boron trifluoride (BF3), ferric chloride (FeCl3), zinc chloride (ZnCl2), titanium tetrachloride (TiCl4), tin trichloride (SnCl4), antimony pentachloride (SbCl5) or ferric bromide (FeBr3); the organic solvent is one or more of fluoroethylene carbonate and dimethyl carbonate, ethyl methyl carbonate or ethylene glycol dimethyl ether;
[0044] (2) Under an inert gas protection and anhydrous environment, the precursor solution is added to the silicon-based powder electrode and allowed to stand to allow the precursor solution to fully infiltrate the powder electrode and penetrate into the gaps in the powder electrode to fully contact with the various components of the electrode;
[0045] (3) Heating at 25-100° C. to initiate an in-situ ring-opening polymerization reaction of the polymer monomer to obtain an organic-inorganic hybrid. The organic-inorganic hybrid tightly connects the components in the powder electrode to construct a mechanically stable electrode structure and forms an artificial SEI film with a rich structure on the electrode surface. Fig.10 shown.
[0046] A lithium battery is used as an example below, and the silicon-based electrode is used as a negative electrode to make a lithium-ion battery.
[0047] Example 1
[0048] In Example 1 of the present invention, a lithium-ion battery is prepared by using a silicon-based electrode with a reinforced structure for a lithium battery as a negative electrode, comprising the following steps:
[0049] Step (1): negative electrode slurry is formed by mixing negative electrode active material submicron silicon particles, conductive agent carbon black, and binder polyacrylic acid in a weight ratio of 8:1:1, and the slurry is coated on a negative electrode current collector Cu foil, and a negative electrode sheet is obtained after drying and rolling, and a 400 μm lithium sheet is used as a counter electrode;
[0050] Step (2): In an argon protective atmosphere with an oxygen content and a water content of less than 1 ppm, 6.85 wt% of 1,3,5-trioxane, 69.31 wt% of fluoroethylene carbonate and 23.84 wt% of LiODFB were mixed to obtain a uniform precursor solution. The precursor solution was heated to 20 ul / mg / cm 2 Add the standard amount of MgO2 to the powder electrode (negative electrode), let it stand to fully soak, heat the fully soaked electrode to initiate polymerization reaction, and obtain a structurally reinforced silicon-based electrode (negative electrode). Figure 1 As shown in (b, d), after in-situ polymerization, the voids inside the enhanced silicon-based electrode Si are filled with polymer, and the Si particles are wrapped by the buffer matrix. Fourier transform infrared spectroscopy (FTIR) was used to characterize the changes in functional groups before and after polymerization, as shown in Figure 3 As shown; X-ray photoelectron spectroscopy (XPS) analysis was used to characterize the composition of the RI-Si electrode surface, as shown Figure 4 As shown, the presence of silicon active particles, poly 1,3,5-trioxane, LiF, BO and FB components is shown.
[0051] Step (3): The silicon-based electrode and the counter electrode prepared in step (2) are assembled into button cells in a glove box with a water and oxygen content of less than 1 ppm, and the electrolyte is injected into the silicon-based electrode and the diaphragm, and the counter electrode lithium sheet, the diaphragm and the negative electrode sheet (silicon-based electrode) are encapsulated in the battery shell to obtain a lithium battery containing a structurally reinforced silicon-based electrode. The electrolyte formula is 1.0M LiPF6 dissolved in a mixed solution of ethylene carbonate / dimethyl carbonate (EC / DMC (volume ratio 1:1)), and 10% FEC is added as an additive.
[0052] Battery test: Constant current charge and discharge cut-off voltage is 0.01-1.5 V. The first five cycles are charged and discharged at a rate of 0.2 A / g, and the subsequent cycles are charged and discharged at a rate of 1.0 A / g.
[0053] Peel force test: Cut the silicon-based electrode obtained in step (2) into 12×60 mm 2 size, stick 3M double-sided tape of the same specification on the rectangular stainless steel plate, and make sure that the tape is tightly bonded to the steel plate. Then, accurately fit the electrode (active material side) to the other side of the tape. Place a part of the steel plate in the fixture under the universal testing machine and clamp it vertically to the ground. Gently tear it from the bottom to the middle of the electrode, then bend it 180° and clamp it to the upper fixture of the machine. By adjusting the position of the fixture on the machine, perform a peel test at a speed of 20cm / min, and record the displacement and applied force on the horizontal and vertical coordinates respectively. Fig.12 As shown, the average peeling force of the silicon-based electrode in Example 1 is 15.74N.
[0054] Comparative Example 1
[0055] The lithium ion battery of Comparative Example 1 comprises the following steps:
[0056] Step (1): Mix the negative electrode active material submicron silicon particles, the conductive agent carbon black, and the binder polyacrylic acid in a weight ratio of 8:1:1 to form a negative electrode slurry, and apply the slurry on the negative electrode current collector Cu foil, and obtain the negative electrode sheet after drying and rolling, and use a 400μm lithium sheet as the counter electrode. Figure 1 As shown in (a, c), the interior of the silicon electrode is a traditional porous powder electrode structure.
[0057] Step (2): The negative electrode and the counter electrode prepared in step (1) are assembled into button cells in a glove box with a water and oxygen content of less than 1 ppm, and the electrolyte is injected into the negative electrode and the separator. The counter electrode lithium sheet, the separator and the negative electrode are encapsulated in the battery shell, and the lithium battery is completed. The electrolyte formula is 1.0M LiPF6 dissolved in a mixed solution of ethylene carbonate / dimethyl carbonate (EC / DMC (volume ratio 1:1)), and 10% FEC is added as an additive.
[0058] Battery test: Constant current charge and discharge cut-off voltage is 0.01-1.5 V. The first five cycles are charged and discharged at a rate of 0.2 A / g, and the subsequent cycles are charged and discharged at a rate of 1.0 A / g.
[0059] like Figure 2 As shown in (a, b), the digital photos respectively show the different surface smoothness of the negative electrodes of Comparative Example 1 and Example 1. Figure 2 The electrode surface of b is flat and smooth, indicating that the polymer uniformly fills the gaps inside the electrode Si and covers the surface of the RI-Si electrode to form a rich artificial SEI layer, which significantly improves the mechanical stability of the electrode structure.
[0060] The battery test results of Example 1 and Comparative Example 1 are as follows: Figure 5 As shown: the electrode in Example 1 still retains a high specific capacity of 1984.3 mAh / g after 300 cycles at 1.0 A / g, and the capacity retention rate is 83.9%. In contrast, the capacity of the electrode in Comparative Example 1 drops rapidly to almost zero after 200 cycles.
[0061] Peeling force test: Cut the negative electrode sheet obtained in step (1) into 12×60 mm 2 size, stick 3M double-sided tape of the same specification on the rectangular stainless steel plate, and make sure that the tape is tightly bonded to the steel plate. Then, accurately fit the electrode (active material side) to the other side of the tape. Place a part of the steel plate in the fixture under the universal testing machine and clamp it vertically to the ground. Gently tear it from the bottom to the middle of the electrode, then bend it 180° and clamp it to the upper fixture of the machine. By adjusting the position of the fixture on the machine, perform a peel test at a speed of 20cm / min, and record the displacement and applied force on the horizontal and vertical coordinates respectively. Fig.12 As shown, the average peeling force of the negative electrode sheet in Comparative Example 1 is 11.35N.
[0062] Example 2
[0063] In Example 2 of the present invention, a lithium-ion battery is prepared by using a silicon-based electrode with a reinforced structure for a lithium battery as a negative electrode, comprising the following steps:
[0064] Step (1): Step (1): Submicron silicon particles of negative electrode active material, carbon black of conductive agent, and polyacrylic acid of binder are mixed in a weight ratio of 8:1:1 to form a negative electrode slurry, and the slurry is coated on the negative electrode current collector Cu foil, and the negative electrode sheet is obtained after drying and rolling; LiNi cobalt manganese oxide of positive electrode active material is mixed. 0.8 Co 0.1 Mn 0.1The positive electrode slurry formed by mixing O2 (NCM811), conductive agent carbon black, and binder polyvinylidene fluoride in a weight ratio of 8:1:1 is coated on the positive electrode collector A1 foil, and the positive electrode sheet is obtained after drying and rolling.
[0065] Step (2): In an argon protective atmosphere with an oxygen content and a water content of less than 1 ppm, 6.85 wt% of 1,3,5-trioxane, 69.31 wt% of fluoroethylene carbonate and 23.84 wt% of LiODFB were mixed to obtain a uniform precursor solution. The precursor solution was heated to 20 ul / mg / cm 2 Add the standard amount of 20% to the powder electrode (negative electrode) and let it stand for full infiltration. Heat the fully infiltrated electrode to initiate polymerization reaction, and obtain the silicon-based electrode (negative electrode).
[0066] Step (3): The silicon-based electrode and the positive electrode obtained in step (2) are assembled into a button cell in a glove box with a water and oxygen content of less than 1 ppm, and the electrolyte is injected into the silicon-based electrode and the diaphragm, and the positive electrode, the diaphragm and the negative electrode are encapsulated in the battery housing to obtain a lithium battery containing a structurally reinforced silicon-based electrode. The electrolyte formula is 1.0M LiPF6 dissolved in a mixed solution of ethylene carbonate / dimethyl carbonate (EC / DMC (volume ratio 1:1)), and 10% FEC is added as an additive.
[0067] Battery test: Constant current charge and discharge cut-off voltage is 2.5-4.3V. The first five cycles are at 0.2mA / cm -2 The subsequent cycles were charged and discharged at 0.5 mA / cm -2 Charge and discharge under the conditions of rate.
[0068] Comparative Example 2
[0069] The lithium ion battery of Comparative Example 2 comprises the following steps:
[0070] Step (1): Submicron silicon particles of negative electrode active material, carbon black of conductive agent, and polyacrylic acid of binder are mixed in a weight ratio of 8:1:1 to form a negative electrode slurry, and the slurry is coated on a negative electrode current collector Cu foil, and a negative electrode sheet is obtained after drying and rolling; LiNi cobalt manganese oxide of positive electrode active material is mixed; 0.8 Co 0.1 Mn 0.1 The positive electrode slurry formed by mixing O2 (NCM811), conductive agent carbon black, and binder polyvinylidene fluoride in a weight ratio of 8:1:1 is coated on the positive electrode collector A1 foil, and the positive electrode sheet is obtained after drying and rolling.
[0071] Step (2): Assemble the negative electrode and positive electrode obtained in step (1) into button cells in a glove box with a water and oxygen content of less than 1 ppm, inject electrolyte into the negative electrode and the separator, and package the positive electrode, separator and negative electrode in the battery shell to complete the lithium battery. The electrolyte formula is 1.0M LiPF6 dissolved in a mixed solution of ethylene carbonate / dimethyl carbonate (EC / DMC (volume ratio 1:1)), and add 10% FEC as an additive.
[0072] Battery test: Constant current charge and discharge cut-off voltage is 2.5-4.3V. The first five cycles are at 0.2mA / cm -2 The subsequent cycles were charged and discharged at 0.5 mA / cm -2 Charge and discharge under the conditions of rate.
[0073] The battery test results of Example 2 and Comparative Example 3 are as follows: Figure 6 As shown, the Si / / NCM811 battery in Example 2 has a 2 After initial activation for 5 times at 0.5 mA / cm 2 A relatively stable 1.1 mAh / cm 2 The capacity retention rate after 200 cycles is 85.5%. The capacity retention rate of the Si / / NCM811 battery in Comparative Example 3 is only 38.6% after 200 cycles.
[0074] Example 3
[0075] The preparation steps are consistent with those in Example 1, except that the polymer monomer used to prepare the precursor solution is 1,3-dioxolane. Figure 7 is a scanning electron microscope image of a cross section of a silicon-based electrode of Example 3, showing that the pores in the electrode are filled with an organic-inorganic hybrid; Figure 8 The Fourier transform infrared spectra of the polymer monomers in Example 3 before and after polymerization prove that polymerization has occurred.
[0076] Battery test: Constant current charge and discharge cut-off voltage is 0.01-1.5 V. The first five cycles are charged and discharged at a rate of 0.2 A / g, and the subsequent cycles are charged and discharged at a rate of 1.0 A / g.
[0077] The battery test results of Example 3 are as follows: Fig. 9 As shown, the silicon electrode in Example 3 still retains a high specific capacity of 1662.3 mAh / g after 200 cycles at 1.0 A / g, and the capacity retention rate is 90.1%
[0078] Example 4
[0079] The preparation steps are consistent with those of Example 3, except that the ring-opening catalyst used in preparing the precursor solution is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0080] Battery test: Constant current charge and discharge cut-off voltage is 0.01-1.5 V. The first five cycles are charged and discharged at a rate of 0.2 A / g, and the subsequent cycles are charged and discharged at a rate of 1.0 A / g.
[0081] The battery test results of Example 4 are as follows: Fig.10 As shown: the silicon electrode in Example 4 still retains a high specific capacity of 1081.4 mAh / g after 50 cycles at 1.0 A / g, and the capacity retention rate is 87.5%.
[0082] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a structurally reinforced silicon-based electrode for a lithium battery, characterized in that: The following steps are involved: (1) Mixing 5% to 10% of a polymer monomer, 1% to 25% of a ring-opening catalyst and 65% to 94% of an organic solvent by mass fraction to obtain a precursor solution, wherein the polymer monomer is one or more of 1,2-propylene oxide, 1,3-dioxolane or 1,3,5-trioxane, and the ring-opening catalyst is one or more of lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, anhydrous aluminum chloride, boron trifluoride, ferric chloride, zinc chloride, titanium tetrachloride, tin trichloride, antimony pentachloride or ferric bromide; (2) Under an inert gas protection and anhydrous environment, the precursor solution is added to the silicon-based powder electrode and allowed to stand to allow the precursor solution to fully infiltrate the powder electrode and penetrate into the gaps in the powder electrode to fully contact with the various components of the electrode; (3) Heating at 25 to 100° C. to initiate an in-situ ring-opening polymerization reaction of the polymer monomer to obtain an organic-inorganic hybrid. The organic-inorganic hybrid tightly connects the components in the powder electrode to construct a mechanically stable electrode structure and form a rich artificial SEI film on the electrode surface.
2. The method for preparing a silicon-based electrode according to claim 1, characterized in that: The polymer monomer is 1,3-dioxolane or 1,3,5-trioxane.
3. The method for preparing a silicon-based electrode according to claim 2, characterized in that: The ring-opening catalyst is lithium difluorooxalate borate or lithium bis(trifluoromethanesulfonyl)imide.
4. The method for preparing a silicon-based electrode according to claim 1, characterized in that: Calculated by mass fraction, the amount of the polymer monomer used is 6.85%, the amount of the ring-opening catalyst used is 23.84%, and the amount of the organic solvent used is 69.31%.
5. The method for preparing a silicon-based electrode according to claim 1, characterized in that: The organic solvent is one or more of fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate or ethylene glycol dimethyl ether.
6. The method for preparing a silicon-based electrode according to claim 1, characterized in that: Step (2) is carried out in a glove box under argon protection with water content and oxygen content both less than 1 ppm.
7. The method for preparing a silicon-based electrode according to claim 1, characterized in that: It is characterized in that The heating temperature in step (3) is 80°C.
8. A silicon-based electrode produced by the method for producing a silicon-based electrode according to any one of claims 1 to 7.
9. Use of the silicon-based electrode according to claim 8 in lithium batteries.
10. A lithium battery, characterized in that: It includes using the silicon-based electrode described in claim 8 as a negative electrode.
Citation Information
Patent Citations
Silicon-carbon negative electrode material and preparation method thereof
CN110931744A
Current collector, electrode plate comprising same and electrochemical device
CN115799522A
Low-temperature silicon-based negative electrode compatible polymer electrolyte, preparation method thereof and lithium ion battery
CN117855599A
Electrolyte, electrode, and battery
JP2007042387A
Electrolytes for silicon-containing electrodes
US20240250301A1